Galactic cosmic rays-clouds effect and bifurcation model of Earth global climate - Rusov, V.D.; Glushkov, A.V.; Vaschenko, V.N.; Zelentsova, T.N.; Mihalys, О.T.; Khokhlov, V.N.; Kolos, A.; Patlashenko, Zh. (Український антарктичний журнал, 2006)
The possible physical linkage between the cosmic rays cloud and indirect aerosol effects is discussed using the analysis of the first indirect aerosol effect (Twomey effect) and its experimental representation as the dependence of mean cloud droplet effective radius versus aerosol index defining the column aerosol number. It is shown that the main kinetic equation of Earth climate energy-balance model is described by the bifurcation equation (relative to the surface temperature of the Earth) in the form of fold catastrophe with two controlling parameters defining the variations of insolation and Earth magnetic field (or cosmic rays intensity in the atmosphere) respectively. The results of comparative analysis on the time-dependent solution of Earth climate energy-balance model taking into account nontrivial role of galactic cosmic rays and the known experimental data on the paleotemperature from the Vostoc ice core are presented. In the framework of the bifurcation model (i) the possibility of abrupt glacial climate changes analogous to the Dansgaard-Oeschger events due to stochastic resonance is theoretically argued, (ii) the concept of the climatic sensitivity of water (vapour and liquid) in the atmosphere is introduced. This concept reveals the property of temperature instability in the form of so-called hysteresis loop. On the basis of this concept it is shown that the simulated time series of global ice volume over the past 730 kyr are in good agreement with time series of seawater δ¹⁸O (ice volume proxy). (iii) Also, the so-called "doubling CO₂" problem is discussed.